2017
DOI: 10.1186/s13024-017-0219-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale network modeling of oligodendrocytes reveals molecular components of myelin dysregulation in Alzheimer’s disease

Abstract: BackgroundOligodendrocytes (OLs) and myelin are critical for normal brain function and have been implicated in neurodegeneration. Several lines of evidence including neuroimaging and neuropathological data suggest that Alzheimer’s disease (AD) may be associated with dysmyelination and a breakdown of OL-axon communication.MethodsIn order to understand this phenomenon on a molecular level, we systematically interrogated OL-enriched gene networks constructed from large-scale genomic, transcriptomic and proteomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 107 publications
(138 citation statements)
references
References 95 publications
(119 reference statements)
8
129
1
Order By: Relevance
“…A previous study investigating the relationship of a similar myelin/oligodendrocyte mRNA brain co-expression module to AD found that expression of this module decreased in both AD and PSP in temporal cortex, with stronger changes in PSP 76 . Another mRNA network study observed downregulation of oligodendrocyte module hubs in AD 77 . We observed an increase in this module in AD, with no changes in PSP.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…A previous study investigating the relationship of a similar myelin/oligodendrocyte mRNA brain co-expression module to AD found that expression of this module decreased in both AD and PSP in temporal cortex, with stronger changes in PSP 76 . Another mRNA network study observed downregulation of oligodendrocyte module hubs in AD 77 . We observed an increase in this module in AD, with no changes in PSP.…”
Section: Discussionmentioning
confidence: 97%
“…The discrepancy in our findings may relate to possible differences between DLPFC and temporal cortex in this co-expression module, differences in module membership that may be important for disease relationship, or a divergence between mRNA and protein expression in M2 module members. In fact, the basis for disease causality regarding the M2 myelin/oligodendrocyte module may relate more to dysregulation of module member co-expression, rather than to the actual change in direction of expression 77 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations